Soil properties of overburden and topsoil in limestone mining area: A preliminary study - Hindersah, Reginawanti; Mauludy, Noor Muhammad; Sumbada, Rifyal Achmad Rivaldi; Sandrawati, Apong; Arifin, Mahfud (Brawijaya University, 2024)
Limestone mining removes topsoil and produces overburden piles, which is improper for plant growth. The objectives of this study were to compare the texture, certain chemical properties, and bacterial population of overburden to the topsoil and to observe the effects of compost amendment on the growth of corn seedlings on the potted overburden. The overburden characterization was performed using a quantitative descriptive method with purposive sampling. Samples were taken from a 6-month-old overburden pile and a pine-vegetable agroforestry ecosystem. The data were further analyzed by using the Student’s t-test. A bioassay was set up in a randomized block design with various concentration compost treatments and five replications. The results showed significant differences between texture, chemical characteristics, and bacterial counts of overburden and topsoil were recorded. The topsoil was more acidic and had higher organic carbon, potential phosphorus, potential potassium, and cation exchange capacity, while the overburden had higher levels of calcium; however, the total N and Magnesium content in topsoil and overburden was similar. The bacterial population of the overburden was lower than in the topsoil. A total of 16 gram-negative and one gram-positive bacteria have been identified from both samples. Applying huge amounts of compost enhanced corn seedlings' growth in the overburden. The study suggested that overburden was more unfertile compared to the topsoil. Therefore, the improvement of overburden properties by compost amendment is needed to green the area.